Effect of Fortification of Tuna Fish Bone Flour with Different Concentrations on Calcium Content and Organoleptic Quality of Tuna Fish Porridge Canned - Baba, Muhrim; Haya, Usman; K. Bunga, Jelsi; Tangke, Umar (Agrikan Jurnal Agribisnis Perikanan, 2021)
This study aims to analyze the organoleptic quality and calcium content of canned tuna porridge with fortification of tuna bone meal at different concentrations and determine the appropriate tuna bone meal concentration formula as a fortification agent in canned tuna fish porridge. This research is a type of empirical research conducted in the Lab. Processing of Fishery Products and continued with the process of testing the calcium content of the product in the Lab. PT. Angler BioChambLab. The results of the organoleptic quality analysis of canned tuna porridge showed that the fortification of tuna bone meal had a significant effect with the calculated F value and P-value/significance of each texture 19.17, 0.0025., color 262.181, 0.000., odor 23.147, 0.002 and taste. 243,000, 0.000. while the results of the calcium test showed that the fortification of tuna bone meal could increase the calcium content with the value of each treatment being 102 mg/kg for the control treatment, 869 for the A1 treatment (3%) and 1,621 mg/kg for the A2 treatment (6%). ). For the best product, the results of the analysis using the Bayes method, it was found that the A1 treatment was the best treatment, this was supported by the calcium value that was still good for the daily requirement of 1000 mg/kg.